2020
DOI: 10.3389/fsufs.2020.00019
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Efficacy of Two Triple-Wash Procedures With Sodium Hypochlorite, a Lactic–Citric Acid Blend, and a Mix of Peroxyacetic Acid and Hydrogen Peroxide to Inactivate Salmonella, Listeria monocytogenes, and Surrogate Enterococcus faecium on Cucumbers and Tomatoes

Abstract: This study was designed to evaluate two triple-wash procedures with commercial antimicrobials to inactivate foodborne pathogens and surrogate bacteria on cucumbers and tomatoes. Fresh, West Virginia locally grown cucumbers and tomatoes were dip-inoculated with Salmonella Typhimurium and Tennessee, Listeria monocytogenes (3-strain), and Enterococcus faecium. Produce was washed through two triple-wash steps (10 s each) including water dip, antimicrobial dip, and water dip (WAW), or water dip, water dip, and anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The inoculated cucumbers had a relatively smooth surface and did not have a stem or calyx section; this potentially indicates that the use of a sanitizer with or without bubbles may be sufficient to remove L. innocua from the surface of this produce. A previous study reported that 100 ppm of chlorinated water was effective in reducing the population of L. monocytogenes in cucumbers and tomatoes [ 36 ]. Another study involving the intentional introduction of bacteria to fresh tomatoes revealed that immersing them in a 200 ppm chlorine solution for 15 min led to an 8.06 log reduction of E. coli from the tomato surfaces, while dipping lettuce leaves in a 100 ppm chlorine solution resulted in a 3.00 log reduction of Salmonella spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inoculated cucumbers had a relatively smooth surface and did not have a stem or calyx section; this potentially indicates that the use of a sanitizer with or without bubbles may be sufficient to remove L. innocua from the surface of this produce. A previous study reported that 100 ppm of chlorinated water was effective in reducing the population of L. monocytogenes in cucumbers and tomatoes [ 36 ]. Another study involving the intentional introduction of bacteria to fresh tomatoes revealed that immersing them in a 200 ppm chlorine solution for 15 min led to an 8.06 log reduction of E. coli from the tomato surfaces, while dipping lettuce leaves in a 100 ppm chlorine solution resulted in a 3.00 log reduction of Salmonella spp.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the results of a study by Li et al, (2020) that compared the efficacy of different washing procedures on cucumber and tomatoes. Findings from this study suggested that the antimicrobial efficacy of chlorinated water at a concentration of 100 ppm significantly removed Salmonella spp., regardless of the produce type [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our analysis of Efm from all sources revealed no significant association between MIC PAA and minimum growth pH or between MBC PAA and minimum survival pH (p > 0.05) (Figure 7). (e) (f) As far as we know, there are limited studies showing the susceptibility of Efm populations to PAA, and they use diverse methodological strategies [40,55,56], which makes it difficult to compare our data with isolates from other collections. However, this study shows that Efm can survive above the minimum concentration of PAA used in the food chain (20 mg/L sanitation of automatic spraying in closed systems; 125 mg/L hand disinfection) and in the clinical settings (125 mg/L hand disinfection in hospitals, health and animal care areas) [8].…”
Section: Enterococcus Faeciummentioning
confidence: 99%